Keramikken fra Barmer - Kock, Jan (Hikuin, 2001)
The pottery from Barmer By Jan Kock Considerable pottery has been found in and around kilns I and II, all made of fine, sand-tempered clay. Almost all the pottery is coil built and pressed up. The main forms are bowls with a rounded body and base and out-bent rims, bowls with strongly profiled rims and shoulders, bowls with in-bent openings, pots with a rounded body and base, smaller pots, also with a rounded body and base, and finally, a small number of jugs. All the pottery is greyish brown to grey, sand-tempered ware and fired to varied degrees of hardness. Everything indicates that it was intended to produce fairly hard-fired, reduction-fired ware. The C-14-dating and the occurrence of very similar vessels from a nearby castle mound whose construction can be dendrochronologically dated to the last quarter of the 14th century allow for a clear dating of when the Barmer potter was active. A comparative analysis of the clay used for the pottery from the two places is exactly the same and this qualifies the dating. The analysis was made by Kaare Lund Rasmussen.